New 6(17)-epoxylathyrane diterpene: aellinane from Euphorbia aellenii induces apoptosis via mitochondrial pathway in ovarian cancer cell line. (13th October 2017) - Nabatchian, Fariba; Moradi, Afshin; Aghaei, Mahmoud; Ghanadian, Mustafa; Jafari, Seyyed Mehdi; Tabesh, Samineh
Abstract: Euphorbia species have been used in traditional medicine in many countries for the treatment of cancer. This article aims to evaluate the capability of a new lathyrane diterpene isolated from Euphorbia aellenii to induce apoptosis in the Caov-4 cell line to determine the underlying mechanism of its anticancer effects. A new 6(17)-epoxylathyrane diterpenes: aellinane from Euphorbia aellenii was evaluated for viability of Caov-4 cells by MTT method. Apoptosis induction by lathyrane diterpene was confirmed by annexin V-FITC/PI staining, and caspase-6 activation. The Bcl2 and Bax protein content were detected by Western blot analysis. Finally, we employed the fluorescent ROS detection kit and fluorochrome JC-1 to determine ROS levels and loss of mitochondria membrane potential (ΔΨm) in Caov-4 cells, respectively. The results show that lathyrane diterpene has significant cytotoxic effect against Caov-4 cells. The IC50 value was 45 μM. Annexin V/propidium iodide (PI) staining and caspase-6 activity assay confirmed that lathyrane diterpene is able to induce apoptosis in Caov-4 cells. The results also demonstrate that lathyrane diterpene up-regulated Bax and down-regulated Bcl-2 proteins. Moreover, apoptotic effect of lathyrane diterpene was also related to ROS production and loss of mitochondrial membrane potential (ΔΨm). This study demonstrated that lathyrane diterpene has profound activity against Caov-4 cells. Analysis of apoptosis-related proteins revealed that lathyrane diterpene triggered the mitochondrion-mediated apoptosis pathway, which led to the loss of mitochondrial membrane potential (ΔΨm) and activation of caspase-6. Therefore, we believe that lathyrane diterpene might be a promising natural compound in ovarian cancer therapy.